2007
DOI: 10.1042/ba20070115
|View full text |Cite
|
Sign up to set email alerts
|

Violacein: properties and biological activities

Abstract: The violet pigment violacein is an indole derivative, isolated mainly from bacteria of the genus Chromobacterium, which exhibits important antitumoral, antimicrobial and antiparasitary properties. Furthermore, the formulation of violacein in different polymeric carriers developed so far offers alternative approaches to overcoming physiological barriers and undesirable physicochemical properties in vivo, thus improving its efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(61 citation statements)
references
References 45 publications
0
61
0
Order By: Relevance
“…Nearly 63% of commercially available drugs are directly or indirectly derived from microorganisms, plants and animals [23]. Several studies have reported the beneficial effect of violacein as an anti-parasitic, antitumor, and agent [1, 2]. Violacein is a potentially interesting therapeutic candidate as an anti-inflammatory and anti-tumor agent because of its effect towards antagonizing the pro-inflammatory cytokine effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly 63% of commercially available drugs are directly or indirectly derived from microorganisms, plants and animals [23]. Several studies have reported the beneficial effect of violacein as an anti-parasitic, antitumor, and agent [1, 2]. Violacein is a potentially interesting therapeutic candidate as an anti-inflammatory and anti-tumor agent because of its effect towards antagonizing the pro-inflammatory cytokine effect.…”
Section: Discussionmentioning
confidence: 99%
“…Violacein has been suggested to exert various biological properties including anti-cancer, anti-inflammatory, anti-bacterial, and anti-parasitic activities [2]. The complex ring structure of violacein renders it hydrophilic and thus with a potential to pass through the cell membrane with greater efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…A number of potential virulence factor genes were found that may contribute to insect toxicity, including production of the pigment violacein (8), homologs of Mycobacterium virulence operons (9), nonribosomal peptide synthesis siderophores, hydrogen cyanide (10), type III secretion system-associated effectors, chitin binding protein, and secreted chitinases (11, 12). MWU2387 contains 15 probable chitinase genes, including four probable chitinase A genes and 10 endochitinases.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Research on pharmaceutical applications of C. violaceum have been carried out since the 1970’s with reported production of antitumor peptides, compounds with analgesic and antibiotic capability [3-5], and synthesis of biodegradable polymers [6]. C. violaceum’s hallmark is the production of the purple pigment violacein that has innumerous therapeutic properties such as anti-tumoral activity [7]. …”
Section: Introductionmentioning
confidence: 99%